2016
DOI: 10.1080/08952841.2015.1018030
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived health status, gender, and work status

Abstract: This study analyzes the relationship between gender and self-perceived health status in Spanish retirees and housewives from a sample of 1,106 community-dwelling older adults. A multivariate linear regression model was used in which self-perceived health status was measured by the EQ-5D visual analogue scale and gender according to work status (retired men and women and housewives). Retired males reported a significantly better health status than housewives. Self-perceived health status was closely associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 24 publications
4
11
0
1
Order By: Relevance
“…Perceived health status was associated with lower disability and fewer chronic diseases, sleeping well, increased weekly exercise, and healthy eating (Mediterranean diet) including a moderate drinking of wine or beer during meals. Similar associations have been found in other studies, where perceived health was found to be strongly associated with physical and functional health, among others [26].…”
Section: Discussionsupporting
confidence: 91%
“…Perceived health status was associated with lower disability and fewer chronic diseases, sleeping well, increased weekly exercise, and healthy eating (Mediterranean diet) including a moderate drinking of wine or beer during meals. Similar associations have been found in other studies, where perceived health was found to be strongly associated with physical and functional health, among others [26].…”
Section: Discussionsupporting
confidence: 91%
“…The study showed that the older persons felt restricted by their diseases because their choices of activities were reduced and they felt lonely and isolated [ 35 ]. Other studies have reported that not being able to do leisure- and everyday activities was more strongly associated with poor self-rated health than medical diagnoses and chronic diseases [ 13 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tendency of women rating their health poorer than men has also been shown in a longitudinal study in Norway [ 11 ] as well as in a prospective study with data from Europe and USA [ 8 ]. Studies have shown that level of education is associated with self-rated health and that woman with low educational level or no work outside home rated their heath poorer than women with higher education [ 8 , 12 , 13 ]. There are also differences between countries regarding older persons’ self-rated health.…”
Section: Introductionmentioning
confidence: 99%
“…The Eurobarometer (2012) survey revealed that health leads the list of values associated with happiness in all European member states assessed except Denmark, where respondents first mention love. Several studies relate SGH with the human values of Stimulation (e.g., Sagiv and Schwartz 2000), Hedonism (e.g., Pino-Domínguez et al 2016), Achievement (e.g., Minkkinen et al 2017), Power (e.g., Verstraete et al 2018), Security (e.g., Norlander et al 2015), Conformity (e.g., del Pilar Sánchez-López et al 2014), Tradition (e.g., Baiocchi-Wagner andOlson 2016), Benevolence (e.g., Bevan and Sparks 2014), and Universalism (e.g., Hughes 2017).…”
Section: Human Values and Subjective General Health (Sgh)mentioning
confidence: 99%
“…These disci-plines view human values as central to explaining how people select their options and justify their actions, assessing individuals and events and characterising cultural groups and societies (Schwartz 1992(Schwartz , 2012. Values have a significant place in understanding and predicting the motivational bases of attitudes and behaviour decisions (Poeller et al 2018;Schwartz 1992), while transcending specific situations and being unaffected by some variables, namely economic risk (Reeskens and Vandecasteele 2017). To think about human values means thinking about what is important in our life.…”
Section: Introductionmentioning
confidence: 99%